Editorial: Regulating Audit Quality – Ramifications and Research Opportunities. Issue 2 (July 2016) - Moroney, Robyn
Abstract : On taking up the role as an editor of the International Journal of Auditing, I would like to share some thoughts about two current audit quality issues. There is little doubt that audit quality is an issue much discussed and debated by practitioners, regulators and academics. What is less certain is what exactly constitutes a quality audit and how it is best achieved. Regulators, concerned with investor confidence in audited financial statements, have introduced regulations aimed at enhancing audit quality. As audits are unobservable, audit quality is difficult to assess and so evaluating the relative success of different types of regulation can be problematic. With a view to helping readers evaluate research in this area and identify possible research topics, I will focus here on two regulations aimed at enhancing audit quality: partner rotation and audit inspections.